PENGARUH MOTIVASI KERJA TERHADAP SEMANGAT KERJA DAN KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KEPULAUAN MERANTI - Syaifuddin; Indra Prasetyo; Mei Indrawati (Journal of Applied Management and Accounting Science, 2021)
This research aims to analyze and test the impact of work motivation on employee morale, the impact of employee morale on employee performance, the impact of work motivation on employee performance, and the impact of work motivation on employee performance. This research is a type of research that uses an explanatory research model, this research has a quantitative approach using a population of 77 people with details of 32 civil servants and 45 non-civil servants and a sample of 76 people. The analytical method used in this research is path analysis. Based on the test findings, it shows that work motivation has a positive and significant effect on employee morale, employee work enthusiasm has a positive and significant impact on employee work results, work motivation has a positive and significant impact on performance. Work motivation has a positive and significant impact on employee performance through enthusiasm for work.